Overview of EEG Signal Processing for Brain Response to Stimuli - Ravindra, Bhat (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
The brain is one of the most complicated organs in the human body that controls the entire actions/reactions of the body by getting diverse stimuli via the nervous system. The stimulus that is stronger than the threshold stimulus is decoded by the sensory neurons counts creating information on the frequency and the stimulus of the action potentials. This work intends to plan a detailed survey on brain response to stimuli in EEG signal processing by reviewing 35 papers to determine the shortcoming of contributed works. The analysis is exploited in terms of chronological review, and algorithmic analysis. This analysis determines the utilization of diverse models/approaches in the contributed papers. Moreover, the performance parameter analysis along with the best performance is as well stated clearly. Finally, the research gaps and challenges that rely on this topic are clearly described that paves the way for future research contributions.